Political System Of Iran And The challenges Of Relation with The West 1979-2008 - Mohammed Abdul-Rahman Younis Al-Obaydee (دراسات أقليمية, 2010)
Iran West relations Since 1979 has faced so many challenges reflected negatively upon Iran and Participated directly in tension in some periods with a number of European States. These challenges were ideology and Politics adopted by the Iranian regime after 1979 , the crisis of hostages in US. Embassy in Tehran , Exploding u.s. Embassy in Beirut in 1982 , the Case of the British writer Selman Rushdi, the Case of Mikonos restaurant in 1992 , in addition to other Cases like the issue of democratic freedoms , human rights in Iran , opposing peace Process in Middle East , threatening security and Stability of "Israel" and other regional issues , The most important ones is the issue of nuclear program of Iran which is considered at present the basic obstacle stands in front of Iranian – Western relation and hurdles its development.